Precision of the Hologic Horizon A dual energy X-ray absorptiometry in the assessment of body composition. Issue 6 (November 2020) - Cheung, Y.M.; Roff, G.; Grossmann, M.
Highlights: Visceral adipose tissue area (VAT), has been associated with metabolic syndrome as well as cardiovascular disease. Our results suggest the Hologic Horizon A dual energy X-ray absorptiometry is a precise method of providing VAT. Our calculated coefficient of variation for VAT is 2.63% with a least significant change at 95% confidence of 7.28%. The Hologic Horizon A system is a precise and reliable modality to better risk-stratify individuals with obesity. Abstract: Background: As the number of individuals with obesity increases, so too will the demand for a precise, cost-effective and safe method to better risk-stratify this heterogenous population. Visceral adipose tissue (VAT) area, a body composition measurement has been associated with the many facets of the metabolic syndrome. Aim: To determine the precision of dual energy X-ray absorptiometry (DXA) in providing body composition measurements, including VAT area, using the Hologic Horizon A scanner. Method: Thirty participants (mean age 64 years, 47% male), underwent two sequential body composition scans. The coefficient of variation (CV) and least significant change (LSC) were calculated for android/gynoid ratio, appendicular lean/height 2, lean/height 2, total body fat and lean mass, total body mass, and subcutaneous adipose tissue (SAT) and VAT area. Participants were stratified according to age (<70 or ≥70 years), body mass index (BMI) (≤30 kg/m 2 or >30 kg/m 2 ) and sex (male or female). The CV was calculated for each parameter and then analysed for differences between groups. Results: The CV for all parameters was <3% with the exception of SAT (3.86%). The CV of VAT area was 2.63% with a LSC at 95% confidence of 7.28%. Apart from the CV differences between males and females for android/gynoid ratio (male: 3.56% vs. female: 1.74%, p = 0.01) and SAT area (5.04% vs. 2.46%, p = 0.01), there were no significant differences identified between the calculated CV for all other body composition parameters when participants were stratified by age, BMI and sex. Conclusion: DXA scanning, using the Hologic Horizon A system, is capable of providing precise body composition measurements.